The Effects of Omega-3 Fatty Acids and Vitamin E Co-Supplementation on Indices of Insulin Resistance and Hormonal Parameters in Patients with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial - Ebrahimi, Faraneh Afshar; Samimi, Mansooreh; Foroozanfard, Fatemeh; Jamilian, Mehri; Akbari, Hossein; Rahmani, Elham; Ahmadi, Shahnaz; Taghizadeh, Mohsen; Memarzadeh, Mohammad Reza; Asemi, Zatollah (Experimental and Clinical Endocrinology & Diabetes, 2017)
This study was conducted to determine the effects of omega-3 fatty acids and vitamin E co-supplementation on indices of insulin resistance and hormonal parameters in women with polycystic ovary syndrome (PCOS). This randomized double-blind, placebo-controlled trial was done on 68 women diagnosed with PCOS according to the Rotterdam criteria aged 18–40 years old. Participants were randomly assigned into 2 groups to receive either 1 000 mg omega-3 fatty acids from flaxseed oil containing 400 mg α-Linolenic acid plus 400 IU vitamin E supplements (n=34) or placebo (n=34) for 12 weeks. Hormonal parameters were quantified at the beginning of the study and after 12-week intervention. After 12 weeks of intervention, compared to the placebo, omega-3 fatty acids and vitamin E co-supplementation resulted in a significant decrease in insulin (−1.0±3.5 vs. +2.7±6.6 µIU/mL, P=0.004), homeostasis model of assessment-estimated insulin resistance (−0.2±0.8 vs. +0.6±1.5, P=0.005), homeostasis model of assessment-estimated B cell function (−4.3±14.3 vs. +10.5±24.5, P=0.004) and a significant increase in quantitative insulin sensitivity check index (+0.006±0.02 vs. −0.01±0.04, P=0.008). Supplementation with omega-3 fatty acids plus vitamin E led to significant reductions in serum total testosterone (−0.5±0.7 vs. −0.1±0.5 ng/mL, P=0.008) and free testosterone (−1.2±2.1 vs. −0.2±1.7, P=0.04) compared to the placebo group. We did not observe any significant effect of omega-3 fatty acids and vitamin E co-supplementation on fasting plasma glucose and other hormonal profiles. Omega-3 fatty acids and vitamin E co-supplementation for 12 weeks in PCOS women significantly improved indices of insulin resistance, total and free testosterone.
Keywords: supplementation; insulin resistance; hormonal parameters; polycystic ovary syndrome